Polimorfismos de genes pró e anti-inflamatórios candidatos à predisposição à rotura prematura de membranas pré-termo e ao trabalho de parto pré-termo - Ramos, Bruna Ribeiro de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: A genetic predisposition to Preterm Labor (PTL) and Preterm Premature Rupture of Membranes (PPROM) has been suggested; however the relevance of polymorphisms and ancestry to susceptibility to PTL and PPROM in different populations remains unclear. Objective: To evaluate the association between Ancestry Informative Markers (AIM) and Single Nucleotide Polymorphisms (SNPs) in Interleukin-1 beta (IL1B), IL6, IL6 Receptor (IL6R), Tumor Necrosis Factor Alpha (TNFA), TNF Receptor (TNFR), IL10, Toll Like Receptor 2 (TLR2), TLR4, Metalloproteinase 9 (MMP9), Tissue Inhibitors of Metalloproteinase 1 (TIMP1) and TIMP2 genes and the susceptibility to PTL and PPROM in Brazilian women. Patients and Methods: Oral swabs were collected from women with PTL and/or PPROM and their babies (PTL: 137 women and 88 babies; PPROM: 64 women and 44 babies) seen at the Botucatu Medical School's Hospital, between 2003 and 2014. Control group included 402 mother-babies pairs of term deliveries, matched to case group by age and newborn gender. After DNA extraction, AIMs were identified by fragment analysis and SNPs by Taqman® SNP Genotyping Assays (Applied Biosystems) and Polymerase Chain Reaction (PCR). The software Structure v2.3.4 was used to estimate ethnic admixture of mothers. Linkage Disequilibrium and Hardy-Weinberg proportions were tested with Genepop 3.4 and haplotypes inferred using Phase. Mann-Whitney, χ2, Fisher's exact test, Logistic Regression models, Odds Ratio and Manova were used in data analysis. Results: Regarding maternal samples, PTL was associated to European ancestry and smoking and African ancestry was protective. Regarding ancestry analysis, self-reported ethnicity only explained 20% and 15% of the global variation in African and European contributions, respectively. Fetal IL10-592 C and IL10-819 C were also associated to PTL. Maternal alleles IL10-1082 G and TLR2 A increased the risk ...

Introdução: O Trabalho de Parto Pré-Termo (TPP) e a Rotura Prematura de Membranas Pré-Termo (RPM-PT) acarretam severas complicações para o binômio materno-fetal. Entre os fatores de risco associados ao TPP e à RPM-PT, a predisposição genética vem ganhando importância. Contudo, a associação entre genes polimórficos, ancestralidade e a patogênese do TPP e da RPM-PT permanece alusiva. Objetivo: Determinar a associação entre marcadores informativos de ancestralidade (AIMs) e polimorfismos de nucleotídeo único (SNPs) dos genes da Interleucina-1 beta (IL1B), IL6, Receptor de IL6 (IL6R), Fator de Necrose Tumoral Alfa (TNFA), Receptor de TNF alpha (TNFR), IL10, Receptor Toll-like 2 (TLR2), TLR4, Metaloproteinase 9 (MMP9), Inibidor de Metaloproteinase 1 (TIMP1) e TIMP2 maternos e fetais e o TPP e a RPM-PT. Pacientes e Métodos: Foram coletados swabs bucais de gestantes com TPP e/ou RPM-PT e DE seus filhos (TPP: 137 mulheres e 88 filhos; RPM-PT: 64 mulheres e 44 filhos) atendidas no Hospital das Clínicas da Faculdade de Medicina de Botucatu, UNESP, entre os anos de 2003 e 2014. O grupo controle foi constituído por 201 mulheres que tiveram gestações resolvidas a termo e seus 201 filhos, pareadas ao grupo caso por idade materna e sexo do recém-nascido. O DNA total foi extraído dos swabs bucais e submetido à identificação de AIMs por análise de fragmentos e genotipagem de SNPs utilizando Taqman® SNP Genotyping Assays (Applied Biosystems) e Reação em Cadeia da Polimerase (PCR). O software Structure v2.3.4 foi utilizado para estimar mistura étnica materna. Teste de desequilíbrio de ligação e proporção da Hardy-Weinberg foram testados com Genepop 3.4 e haplótipos inferidos com Phase. Os dados sociodemográficos e biológicos foram comparados utilizando os testes de χ2, teste exato de Fisher, Regressão Logística, Manova, Mann-Whitney e Odds Ratio. Resultados: Nas amostras maternas, o TPP foi associado a maior...
Keywords: Hereditariedade; Agentes anti-inflamatórios; Trabalho de parto; Polimorfismo (Genética); Membranas fetais, Ruptura prematura; Genetic polymorphisms; Fetal Membranes, Premature Rupture